Groundwater irrigation and crop economy in the lower Gangetic plain at Matbarer Char, Madaripur, South-Central Bangladesh - Haque, M Aminul; Islam, M Saiful; Zahid, Anwar (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Attempts have been made in this paper to overview the present agricultural inputs for crop production and crop economy in the lower Gangetic plain. Results of the field survey show that the average labour requirement of Boro rice production is 35 person-days/acre. The fertilizer application by the farmers is not balanced and is well below the recommended doses. N, P2O5, K2O ratio used by the farmers was 7:3:1 against the appropriate ratio of 5:4:3 for HYV Boro rice. The cost of Boro rice cultivation has been estimated on the basis of input use. The rice cultivation costs were Tk.14,335, Tk 13,875 and Tk. 11,271 per acre for the water buyer, water seller with diesel pump and water seller with electric pump respectively. Labour and irrigation costs together normally account for two- thirds of the total cost of production - increases in the prices of these inputs can greatly depress Boro rice profitability. Moreover, Gross income of the water sellers from major crops is about 32% higher than that of the water buyers. The study also shows that the total cost for a Shallow Tube Well (STW) run by diesel motive power is almost twice that for electric motive power. If groundwater irrigated agriculture system is framed in a comprehensive manner, this could play an important role in poverty alleviation. DOI: DOI: http://dx.doi.org/10.3329/jasbs.v38i1.15318 J. Asiat. Soc. Bangladesh, Sci. 38(1): 29-39, June 2012